The effects of Aloe vera (Aloe barbadensis) coating on the quality of shrimp during cold storage - Soltanizadeh, Nafiseh (J Food Sci Technol, 2015)
Green tiger shrimp (Penaeus semisulcatus) is an important aquaculture species worldwide. Its perishable nature, however, needs preservation methods to ensure its quality and shelf life. In this study, the effects of Aloe vera coating on the quality and shelf life of shrimps during cold storage were investigated. Shrimp samples were dipped in aqueous solutions containing 25%, 50%, 75%, and 100% Aloe vera gel before storage at 4 °C for 7 days. Drip loss, pH, TBA, TVB-N, and texture of both the control and treated shrimp samples were analyzed periodically. There were significant differences between coated shrimps and the control group in all parameters evaluated. Aloe vera at 75% and 100% concentrations was able to prevent lipid oxidation and drip loss properly; however, coatings containing 25% Aloe vera did not have the desired effects on these characteristics. Shrimps coated with higher concentrations of Aloe vera had better textural properties during cold storage. Results also indicated the positive effects of Aloe vera coating on the sensory quality of shrimp.